2016
DOI: 10.14430/arctic4580
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nestling Mortality in Arctic Peregrine Falcons due to the Biting Effects of Black Flies

Abstract: ABSTRACT. This note describes nestling mortality in Arctic Peregrine Falcons (Falco peregrinus tundrius) due to the biting effects of blood-feeding black flies (Diptera: Simuliidae). At a nest site near Rankin Inlet, Nunavut, Canada (62˚49′ N, 92˚05′ W), a brood of four nestlings died on 20 July 2013 from the direct effects of severe bites attributed to black flies. Within three hours of the onset of blood-feeding, black flies had caused widespread, uniformly distributed hemorrhagic coalescent lesions over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…High exposure and sensitivity without any particular high adaptive capacity 29 make arctic vertebrates particularly vulnerable to parasites 12 , 19 and extreme weather events 3 , 30 . Our results confirm that increased frequency of heavy precipitation can reduce reproductive output of arctic-nesting peregrine falcons directly (through exposure to cold, wet weather), and indirectly through the outbreak of black flies described here and elsewhere 31 . We qualitatively summarized the frequency and severity of these effects on the reproduction of arctic-nesting peregrine falcon during major phases of the breeding cycle (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…High exposure and sensitivity without any particular high adaptive capacity 29 make arctic vertebrates particularly vulnerable to parasites 12 , 19 and extreme weather events 3 , 30 . Our results confirm that increased frequency of heavy precipitation can reduce reproductive output of arctic-nesting peregrine falcons directly (through exposure to cold, wet weather), and indirectly through the outbreak of black flies described here and elsewhere 31 . We qualitatively summarized the frequency and severity of these effects on the reproduction of arctic-nesting peregrine falcon during major phases of the breeding cycle (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Precipitation during the pre-laying period likely triggers the hydrological conditions 33 and nutrient runoff levels 32 required for black fly reproduction. This ultimately results in indirect nestling mortality once adult black flies emerged (this study) and begin blood feeding (i.e., the proximate cause of mortality) on nestlings 31 . During incubation, precipitation directly reduces egg survival (Franke, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Owing to their occasional massive outbreaks and tendency to feed on humans and domestic animals, black flies have caused negative economic impacts on forestry, tourism, and agriculture (Adler and McCreadie 1997). Attacks of black flies have been shown to compromise the breeding efforts of avian breeding pairs through their attacks on adults (Urbanek et al 2010, Solheim et al 2013) and young (Hunter et al 1997, Smith et al 1998, Franke et al 2016). However, no study has yet demonstrated an impact of black flies on a natural avian population (Adler et al 2004).…”
Section: Introductionmentioning
confidence: 99%